Crocodylian remains from the Miocene of the Fore-Carpathian Basin and its foreland—including the world’s northernmost Neogene crocodylian - Marcin Górka; Jakub Březina; Milan Chroust; Rafał Kowalski; Sergi López-Torres; Mateusz Tałanda (Acta Palaeontologica Polonica, 2025)
The geographic distribution of Crocodylia in Europe throughout the Cenozoic experienced fluctuations in the extension of its northern limit. Whereas crocodylians reached very high latitudes during the early Eocene (78ºN), their northward extension was more moderate during almost the entire Paleogene and the Neogene. Here we reassess previous Early-to- Middle Miocene crocodylian records from the Fore-Carpathian Basin and its foreland, namely from marine limestones of Pińczów (Poland), and Židlochovice (Czechia) and from the new vertebrate site of Szczerców (Poland), currently interpreted as a freshwater paleoenvironment. All crocodylian material from these three sites represents Crocodylia indet. and its possible taxonomic attribution is discussed. The new Szczerców specimen, an osteoderm, represents the world’s northernmost record of a crocodylian from the entire Neogene.